Editorial Views on the Research Promotion and Innovation - Chhorn, Than (Journal of Applied Research and Innovation (JARI), 2026)
Research and Innovation were launched as the promotion for students, scholars, and teachers. This suggested researchers disseminating and exchanging the research works/practices and innovation of education, teaching, professional development, language, law, business, economy, psycho-pedagogy, public policy, political science, marketing, and technology. The practitioners were engaged with the critical analysis and discussion of research topics. This aims to motivate researchers or scholars share and innovate research results, which were centralized as the key concepts for policymakers, educators, and academic institutions reform the policies, guidelines or manual works. Research and innovation proffered the supporting initiatives that enhance educational quality, develop the skills, promote multidisciplinary practices, and contribute to the sustainable works.